2020
DOI: 10.18632/aging.102810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotics on cognition, and biomarkers of inflammation and oxidative stress in adults with Alzheimer’s disease or mild cognitive impairment — a meta-analysis of randomized controlled trials

Abstract: Probiotics are live microbes that confer health benefits to the host. Preliminary animal evidence supports the potential role of probiotics in ameliorating cognitive health, however, findings from clinical trials in Alzheimer's disease (AD) or mild cognitive impairment (MCI) subjects are controversial. Thus, a meta-analysis is needed to clarify the efficacy of probiotics on cognition in AD or MCI patients. EMBASE, PubMed, Web of Science and Cochrane library were systematically searched and manually screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 73 publications
0
104
1
1
Order By: Relevance
“…There is increasing research to study the effects of probiotic supplementation in the treatment of mental health and cognitive disorders. A meta-analysis of randomised controlled trials examining patients with both MCI and AD found significant improvements (p ¼ 0.002) in cognition [159]. As well, a meta-analysis found patients with mood disorders receiving probiotic treatment had significantly lower depression scores (SMD ¼ À0.47, 95% CI: À0.67 to À0.27, p¼0.27) without any significant change in anxiety scores [160].…”
Section: Repopulation Of the Gut Microbiome As A New Therapeutic Targmentioning
confidence: 97%
“…There is increasing research to study the effects of probiotic supplementation in the treatment of mental health and cognitive disorders. A meta-analysis of randomised controlled trials examining patients with both MCI and AD found significant improvements (p ¼ 0.002) in cognition [159]. As well, a meta-analysis found patients with mood disorders receiving probiotic treatment had significantly lower depression scores (SMD ¼ À0.47, 95% CI: À0.67 to À0.27, p¼0.27) without any significant change in anxiety scores [160].…”
Section: Repopulation Of the Gut Microbiome As A New Therapeutic Targmentioning
confidence: 97%
“…Additionally, the probiotic intake significantly increased the levels of IL-22 and TRANCE expression at weeks [ 174 ]. A meta-analysis of randomized controlled trials showed that probiotics intake improved cognitive functions in AD and mild cognitive impairment (MCI) subjects, possibly via decreasing the levels of inflammatory and oxidative markers [ 175 ]. In contrast, the meta-analysis of randomized controlled trials showed no remarkable difference between probiotics/prebiotics and placebo in alleviating anxiety and depressive symptoms [ 176 , 177 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…The concept of probiotics as immune modulators and their various applications for preventing, modifying, or treating diseases have been highlighted. Probiotics affect various organs outside the GI tract, and gut-lung crosstalk may be involved in the probiotic-mediated control of acute respiratory infections 30 , 31 . Viral infections in higher vertebrates elicit potent innate and adaptive host immune responses.…”
Section: Discussionmentioning
confidence: 99%